PENGARUH TERAPI BERMAIN MEWARNAI TERHADAP KECEMASAN PADA ANAK PRASEKOLAH DENGAN HOSPITALISASI DI RS GRANDMED LUBUK PAKAM TAHUN 2020 - Kuat Sitepu; Luci Riani Br Ginting; Ratna Bulan Bulan; Sarmana .; Samuel Ginting (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
In general, children who experience hospitalization often experience separation from their parents, children who experience hospitalization must be able to adapt to the new environment and the people around them, the impact of this being cared for and hospitalized is fear around them, anxiety, trauma and anxiety. According to WHO in 2018, almost 52.38% of children experienced hospital treatment. In 2016 in Indonesia as many as 33.2% of 1,425 children experienced the impact of severe hospitalization, 41.6% experienced moderate hospitalization. The National Health Surveillance (SUSENAS), the number of preschool children in Indonesia is 72% of the total population of Indonesia, it is estimated that 35 per 100 children undergo hospitalization and 45% of them experience anxiety. Types and Research Design This research is a quantitative research that is experimental in nature with a Quasi-experimental approach with one group pretest and posttest design. The data analysis of the profitability of the bivariate calculation in this study used a paired sample test at a significance level of 95%. The result of the research is the p value = 0.000, where the p value is <0.05. This shows that the difference before and after doing coloring play therapy on the anxiety of preschool children is very real.